Evaluation of an Anal Insert Device for the Conservative Management of Fecal Incontinence. Issue 9 (September 2015) - Lukacz, Emily S.; Segall, Mark M.; Wexner, Steven D.
Abstract : BACKGROUND: Management of fecal incontinence remains challenging owing to the limited availability of consistently safe, effective, and/or tolerable treatment options. OBJECTIVE: The aim of this study was to evaluate the efficacy, safety, and tolerability of an anal insert device for the conservative management of fecal incontinence. DESIGN: This is a multicenter, prospective, open-label study of a single-arm cohort. SETTING: Patients were recruited between November 2009 and June 2011 from 3 US clinical sites. PATIENTS: Subjects who were ≥18 years old with incontinence severity scores ≥12 of 20, and at least weekly leakage of solid and/or liquid stool, were selected. INTERVENTIONS: Patients underwent 12 weeks of continuous anal insert device use. MAIN OUTCOME MEASURES: The primary outcomes measured were bowel diaries, incontinence severity, satisfaction, and adverse events. The percentage of reduction in leakage frequency and severity was assessed weekly. Sample size calculations predicted that 47 subjects would demonstrate that 70% of subjects would have ≥50% reduction of incontinence frequency. The paired t test and Wilcoxon tests were used as appropriate. RESULTS: Seventy-seven percent of the 73 completers and 62% of the 91 intent-to-treat subjects achieved a ≥50% reduction in incontinence frequency. Median fecal incontinence frequency was reduced by 82% from 0.9 (mean 1.1 ± 0.9) at baseline to 0.2 (mean 0.3 ± 0.4) episodes of leakage per day at 12 weeks ( p < 0.001). Mean fecal incontinence severity scores improved by 32.4% (16.2, ±2.1 vs 10.9, ±4.4 of 20, p < 0.001) and 78% of completers were very or extremely satisfied with the device with no serious adverse events related to device use. LIMITATIONS: This study was limited by the nonvalidated modification of the severity score and the lack of randomization, control comparison group, blinded assessments, and quality-of-life measures. CONCLUSIONS: The anal insert device provides a conservative, safe, and effective management strategy for individuals with fecal incontinence, with high patient satisfaction and low adverse event rates.